Virtual Network Functions placement - ZAIDI, BELQASSIM (UNIVERSITY’S MOHAMED BOUDIAF OF M’SILA Faculty of Mathematics and computer sciences -DEPARTMENT: Computer Science - Option: RTIC, 2019)
Network Functions Virtualization (NFV) is a new network architecture concept virtualizes the network functions such as network address translation, firewalls, encryption, domain name services, caching, … etc. so they can be integrated onto industry standard high volume servers, switches, and storage, which could be in data centers, network nodes, or in the end-user premises. In this context, traditional middlebox appliances are replaced by virtual machines embedding Virtual Network Functions (VNFs). Different VNFs can be chained together to form different service functions chains (SFC) for different network services. Hence, network operators are starting to deploy VNFs to realize network services. In this dissertation, we propose an approach which is based on a greedy heuristic algorithm to find the best placement of SFC to optimize the number of servers hosted. That is leads to optimize network resources utilization and minimizing power consumption.
Keywords: Network Function Virtualization, Virtual Network Functions, service functions chains, greedy algorithm, Virtual Network Functions placement